Austrodontella monticola sp. nov., a new species of Collembola from montane New Zealand - Babenko, Anatoly; Minor, Maria (Zootaxa, 2015)
Collembola were collected from soil in the alpine belt (1600–1900 m a.s.l.) of the Southern Alps of New Zealand. A list of species found is provided. Austrodontella monticola sp. nov., the third species of a Odontellidae genus with a southern distribution is described. The other two species in the genus occur in southern Australia and in the Indian Ocean sector of the Subantarctic respectively. Notes on A. trispina (Womersley, 1935), the type species of the genus, are provided.